African Christian Immigrants - Sackey-Ansah, Alex (Transformation, 2020)
The latent functions of African immigration are often overlooked. Over the years, these functions have produced scenarios worth researching. Many people migrate from Africa to the West looking for greener pastures with the goal of economic upliftment. Amid this venture, however, the African immigrants come along with skills, talents, academic potentials, and religious beliefs. Most African immigrants associate with Christianity and deem it a spiritual mandate from God to impact their sphere of influence during their expeditions. Thus, these groups of immigrants raise churches, form prayer groups, preach the gospel, and create mission fields. The focus of this article is threefold. First, to examine how the religiosity of African Christian immigrants have influenced their lives and in turn impacted the American Christian landscape. Second, how immigration legislation of the United States has revolutionized the lives of African immigrants. Third, how pull and push factors have become a source of motivation for African immigration.